IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA OLEH BADAN PENANGGULANGAN BENCANA DAERAH KOTA SEMARANG KOTA SEMARANG DALAM PENANGANAN BANJIR DAN BANJIR ROB TAHUN 2025 - Ilham Salim Nawawi; Yuwanto Yuwono (Journal of Politic and Government Studies, 2026)
The recurring occurrence of flooding and tidal flooding (rob flooding) in Semarang City indicates that the local government's disaster management capacity has not yet fully addressed the region's vulnerabilities. The districts of Genuk, North Semarang, Tugu, West Semarang, East Semarang, and Gayamsari are threatened by high rainfall, land subsidence, upstream water runoff, and the impacts of tidal flooding. This study aims to examine the role of the Semarang City Regional Disaster Management Agency (BPBD) in flood management in 2025 during the pre-disaster, emergency response, and post-disaster phases, as well as to identify the supporting and inhibiting factors affecting its performance. This study employed a qualitative approach using a case study method through interviews, observations, documentation, and literature review. A disaster management matrix was used to analyze mitigation, preparedness, emergency response, rehabilitation, and reconstruction efforts. The results show that during the pre-disaster phase, the Semarang City BPBD developed various disaster risk reduction measures, including the implementation of an Early Warning System, the Disaster-Safe Education Unit initiative, mitigation training, and risk mapping. In addition, Semarang City has provided flood control infrastructure, such as embankments, retention ponds, and drainage systems. The matrix findings indicate that these programs can enhance community preparedness; however, rapid urbanization, land-use change, and increasing vulnerability in coastal areas hinder their effectiveness. During the emergency response phase, BPBD demonstrated adequate response capacity through the operation of emergency posts, distribution of logistics, deployment of disaster response vehicles and inflatable boats, and cooperation with sub-district governments and related agencies. However, response efforts were uneven across affected areas due to limitations in personnel, operational facilities, and the distance to affected locations. Meanwhile, in the post disaster phase, BPBD carried out rehabilitation and reconstruction efforts to restore the social, economic, and infrastructural conditions of disaster-affected communities. However, recovery efforts remain focused on addressing disaster impacts rather than reducing long-term disaster risk. The findings indicate that the Semarang City BPBD has carried out its duties in accordance with its institutional functions within the disaster management cycle. Nevertheless, its performance continues to be constrained by limitations in institutional capacity and the increasing complexity of flood related risks. The main supporting factors include regulations, early warning systems, infrastructure support, and cross-sectoral cooperation. The inhibiting factors include limitations in operational resources, logistics, human resources, funding, and inter-agency coordination that has not yet been fully integrated. Therefore, strengthening institutional capacity, enhancing stakeholder collaboration, and integrating disaster risk reduction into regional development planning are necessary to improve Semarang City's resilience to flooding and tidal flooding.